2021
DOI: 10.1186/s12909-020-02440-7
|View full text |Cite
|
Sign up to set email alerts
|

How can WhatsApp® facilitate the future of medical education and clinical practice?

Abstract: As part of the modern generation of medical students and prospective future doctors of the United Kingdom’s Nation Health Service (NHS), we have grown up in an age where smartphones and instant messaging applications (IMAs) are ubiquitous across all aspects of society. With IMAs being so familiar, we recognise their scope for facilitating our learning of the pre-registration syllabus and how their practical nature could potentially revolutionise healthcare worldwide. It is, therefore, rational to further inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Studies confirmed that WhatsApp's online group discussions may provide students with a one-point learning and information source (Latif et al, 2019). Current research highlighted WhatsApp can be effective as a medical learning tool (Salam et al, 2021) to facilitate classroom learning and clinical training (Coleman and O'Connor, 2019). Similarly, instant messaging applications can improve "the way medical education is delivered, by creating communication channels between students and tutors, increasing learning opportunities and providing an overall superior educational experience for medical students" (Coleman and O'Connor, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies confirmed that WhatsApp's online group discussions may provide students with a one-point learning and information source (Latif et al, 2019). Current research highlighted WhatsApp can be effective as a medical learning tool (Salam et al, 2021) to facilitate classroom learning and clinical training (Coleman and O'Connor, 2019). Similarly, instant messaging applications can improve "the way medical education is delivered, by creating communication channels between students and tutors, increasing learning opportunities and providing an overall superior educational experience for medical students" (Coleman and O'Connor, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, instant messaging applications can improve "the way medical education is delivered, by creating communication channels between students and tutors, increasing learning opportunities and providing an overall superior educational experience for medical students" (Coleman and O'Connor, 2019). However, there are reports of adverse effects on academic performance with the use of applications such as WhatsApp, Facebook, and games being addictive and stealing students' study time (Salam et al, 2021). Thus, smartphone learning also has challenges (Kim, 2020) along with its many benefits, indicative of its effect on academic performance (Ifeanyi and Chukwuere, 2018;Darko-Adjei, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…WhatsApp is the most popular mode of communication worldwide but its role in medical education still needs further exploration [ 30 ]. Although some studies have recommended WhatsApp use in medical education due to its easy, interactive, and instant role in preparing the students for their day to day learning activities [ 31 , 32 ] its educational effectiveness lacks conclusive evidence [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pre-service health sciences researchers used social media such as Facebook, WhatsApp, and Instagram to link with their class fellows, teachers, and other researchers. Worldwide, governments have partnered with WhatsApp to provide updated information about COVID-19 [ 103 ]. The Pakistan health ministry and many other health agencies also provided ‘real-time’ data about public health and COVID-19 spread on Facebook and Twitter, which was of great concern for health sciences researchers; explicated policies and implementation are needed in this respect.…”
Section: Discussionmentioning
confidence: 99%